Movement analysis in early infancy: Towards a motion biomarker of age. (March 2020) - Marchi, V.; Belmonti, V.; Cecchi, F.; Coluccini, M.; Ghirri, P.; Grassi, A.; Sabatini, A.M.; Guzzetta, A.
Abstract: Background: Early motor development is characterized by progressive changes in general movements paralleled by a gradual organization of the four limbs' repertoire towards the midline, as shown by computerised movement analysis. Aims: Our aim was to test the performance of quantitative computerised kinematic indexes as predictors of post-term age in an independent cohort of typically developing subjects at fidgety age, tested cross-sectionally. Subjects: We selected twelve low risk term infants, who were video recorded between 9 and 20 weeks (fidgety age) during one spontaneous movements session. Study design: We correlated post-term age with I)indexes of coordination including interlimb correlation of velocity and position, II)indexes of distance, including interlimb and limb-to- ground, both expressed as linear distance and as probability of midline limbs position III)indexes of global movement quality by calculating Hjorth's activity, mobility and complexity parameters. All indexes were calculated for both upper and lower limbs. Results: Significant positive correlations were found between post-term age and indexes of distance, and probability of occurrence of upper-limb antigravity patterns, and with both indexes of global movement quality. By combining linear and non-linear parameters related to the upper limb kinematics, we determined individual post-term age with a mean error of <1 week (5.2 days). No correlations were found between age and indexes of coordination. Conclusions: Quantitative computerised analysis of upper-limb movements is a promising predictor of post-term age in typically developing subjects at fidgety age. Highlights: Early motor development is characterized by a progressive organization of the four limbs' movements towards the midline. In typically developing subjects, quantitative indexes of arm movements correlate significantly with post-term age The combination of linear and non-linear movement features provides accurate estimation of age, with an error <1 weeK.